2013
DOI: 10.1039/c3ra42627k
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitchable alkoxy-bridged binuclear rhenium(i) complexes – a potential probe for biomolecules and optical cell imaging

Abstract: Photoswitchable alkoxy-bridged binuclear rhenium(I) complexes -a potential probe for biomolecules and optical cell imaging3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 111 publications
(10 reference statements)
0
21
0
1
Order By: Relevance
“…S10). The decay of absorbing triplet excited state is also bi-exponential with a lifetime of 2.44 µs and t 2 = 0.011 µs for 3, which is not in agreement with the emission lifetime of the low energy band in Fig Several studies have reported triplet energy transfer from a metal ion center to an aryl hydrocarbon, [32][33][34][35][36] but, in some cases, the photosystems were unstable with respect to the sensitized oxygenation of the polycycle 36 . Meyer and co-workers 37 reported an intense transient absorption at 450600 nm, which is characteristic of a 4,4'-bpylocalized MLCT excited state in Re(I) complexes.…”
Section: Time-resolved Absorption Spectramentioning
confidence: 86%
See 2 more Smart Citations
“…S10). The decay of absorbing triplet excited state is also bi-exponential with a lifetime of 2.44 µs and t 2 = 0.011 µs for 3, which is not in agreement with the emission lifetime of the low energy band in Fig Several studies have reported triplet energy transfer from a metal ion center to an aryl hydrocarbon, [32][33][34][35][36] but, in some cases, the photosystems were unstable with respect to the sensitized oxygenation of the polycycle 36 . Meyer and co-workers 37 reported an intense transient absorption at 450600 nm, which is characteristic of a 4,4'-bpylocalized MLCT excited state in Re(I) complexes.…”
Section: Time-resolved Absorption Spectramentioning
confidence: 86%
“…S9), we believe that the excited state decay of 2 originates from the different states, i.e., 3 LLCT/ 3 ILCT excited states. The transient absorption (TA) spectrum of 3 exhibits a bleaching of the MLCT absorption in the region from 420 to 480 nm with a maximum at 460 nm during triplet population 32,33 . In addition, this complex shows a broad and much stronger positive absorption at 500-700 nm (Fig.…”
Section: Time-resolved Absorption Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…[2830], catalysis [31], light-emitting devices [32,33], CO2 fixation [34], optical switches [35,36], bioprobes [37,38] and imaging [39]. As far as we know, there is a limited number of reports available on rhenium(I) complexes attached to the imine ligands [4042].…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%
“…Re(I)‐tricarbonyl diimine complexes are one of the most important and widely studied classes of luminescent d 6 transition metal complexes . The rich photophysical and photochemical behavior of the excited state rhenium(I)‐tricarbonyl complexes led to a wide range of interesting and important applications, including their use as sensors,, catalysts, light‐emitting devices, in CO 2 fixation, electron transfer, energy transfer, optical switches,, bioprobes,, and cellular imaging . The combination of photoactive metal center along with ligand is a desirable candidates for sensing anions.…”
Section: Introductionmentioning
confidence: 99%